Identification of Total Coliform Bacteria in Processed Enbal Food in Several Traditional Markets in Ambon City - Salmin Safril Nahumarury; Melda Yunita; Anggun Lestary Husein; Effendi Effendi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Enbal is a traditional food from Maluku, originally from the Kei Islands, made from bitter cassava (Manihot esculenta). This processed food product holds significant historical and cultural value. However, enbal can become a source of illness if not prepared properly, leading to contamination and an increased risk of foodborne diseases. This study aimed to determine the microbiological quality through total plate count (TPC) analysis and bacterial identification of enbal at several traditional markets in Ambon City. It was a descriptive observational study with a true experimental laboratory approach. The TPC results for enbal food samples from Mardika market ranged from 14.5 × 102 CFU/g to 4.85 × 104 CFU/g, Waiheru market ranged from 8.3 × 102 CFU/g to 3.2 × 105 CFU/g, Batu Merah market ranged from 11.0 × 104 to 3.0 × 105 CFU/g, and Passo market ranged from 2.4 × 102 CFU/g to 3.75 × 105 CFU/g. The results of bacterial species identification from the four enbal food samples revealed Klebsiella pneumoniae and Staphylococcus haemolyticus. Thus, it can be concluded that the four enbal samples examined are safe for consumption as they do not exceed the Indonesian National Standard (SNI) 01-2997-1996, which is 1 x 106 CFU/g.